Programa Rede Mãe Paranaense: pré-natal vivenciado por mulheres residentes em região de fronteira - Oliveira, Thaissy Fernanda de (2019)
Prenatal care stands out as an essential factor in timely interventions on potential risk factors for complications to the health of mothers and their newborns. The relevance of prenatal care for positive outcomes in maternal and infant morbidity and mortality indicators led the State of Paraná to implement the Rede Mãe Paranaense Program (PRMP) in 2012. Objective: To understand the experience of women who underwent prenatal care through PRMP in a border region. Method: It was developed in the municipality of Cascavel and Foz do Iguaçu, located in the West region of Paraná, contemplated in the Border of the Brazilian South Bow on the border with Paraguay and Argentina. The reports were submitted to the analysis process in light of the theoretical reference of the Social Phenomenology of Alfred Schütz. Results: Data collection occurred in the period from May to September 2018, in total 18 women who underwent prenatal care through PRMP participated in the study. From the reports, typifications on prenatal care in the perception of the users were identified, being described in five categories: Knowledge about PRMP; Access and reception in the health service; Multiprofessional service and its peculiarities; Health education and the perspectives of women in relation to the PRMP. Conclusion: The study findings point to a practice focused on the medical-assistance model operated in a systematized manner with little openness to dialogues, exchange of experiences and information. Instigate reflections on prenatal care considering the PRMP proposal, and requires investments in training and actions of professionals in order to optimize the experience of women in a way that is healthy, safe and positive.